Effectiveness and safety of intracranial events associated with the use of direct oral anticoagulants for atrial fibrillation: A systematic review and meta‐analysis of 92 studies. Issue 11 (15th August 2022) - Archontakis‐Barakakis, Paraschos; Li, Weijia; Kalaitzoglou, Dimitrios; Tzelves, Lazaros; Manolopoulos, Apostolos; Giannopoulos, Stefanos; Giamouzis, Grigorios; Giannakoulas, George; Batsidis, Apostolos; Palaiodimos, Leonidas; Ntaios, George; Lip, Gregory Y. H.; et al.
Abstract : Aims: Observational studies have investigated the effectiveness and safety of direct oral anticoagulants (DOACs) and vitamin K antagonists (VKAs) used in nonvalvular atrial fibrillation. We performed a systematic review and meta‐analysis assessing the risk of ischaemic stroke, thromboembolism (TE) and intracranial haemorrhage (ICH) associated with the use of DOACs and VKAs. Methods: Medline and Embase were systematically searched until April 2021. Observational studies were gathered and hazard ratios (HRs) with 95% confidence intervals (CI) were extracted. Subgroup analyses based on DOAC doses, history of chronic kidney disease, stroke, exposure to VKA, age and sex were performed. A random‐effects model was used. Results: We included 92 studies and performed 107 comparisons. Apixaban was associated with lower risk of stroke (HR: 0.82, 95% CI: 0.68–0.99) compared to dabigatran. Rivaroxaban was associated with lower risk of stroke (HR: 0.90, 95% CI: 0.83–0.98) compared to VKA. Dabigatran (HR: 0.85, 95% CI: 0.80–0.91), rivaroxaban (HR: 0.83, 95% CI: 0.77–0.89) and apixaban (HR: 0.75, 95% CI: 0.65–0.86) were associated with lower risk for TE/stroke compared to VKA. Apixaban (HR: 1.32, 95% CI: 1.03–1.68) and rivaroxaban (HR: 1.58, 95% CI: 1.31–1.89) were associated with higher risk of ICH compared to dabigatran. Dabigatran (HR: 0.48, 95% CI: 0.44–0.52), apixaban (HR: 0.60, 95% CI: 0.49–0.73) and rivaroxaban (HR: 0.73, 95% CI: 0.65–0.81) were associated with lower risk of ICH compared to VKA. Conclusion: Our study demonstrated significant differences in the risk of ischaemic stroke, TE/stroke and ICH associated with individual DOACs compared to both other DOACs and VKA.